234k views
0 votes
Complete the following: (r-s)^2 = (___)^2 -(___)rs + s^2

User Darryn
by
6.0k points

1 Answer

2 votes

Answer:

First blank has the value r.

Second blank has the value 2

Explanation:

The given equation on the left side is
( r- s)^(2)

Now, ALGEBRAIC IDENTITY states that


( a- b)^(2) =
a^(2)  + b^(2) -  2 * a * b

Here, comparing a = r and b = s, we get


( r- s)^(2) =
r^(2)  + s^(2) -  2 * r * s

So, the first blank has the value r.

Second blank has the value 2

User Blaque
by
5.6k points